Lawrie's meat science - Lawrie, R. A. (Woodhead Publishing series in food science and technology, 1998)
Contents: Factors affecting the growth and development of meat animals (cattle, sheep and pigs); The structure and growth of muscle; Chemical and biochemical constitution of muscle; The conversion of muscle to meat; The spoilage of meat by infecting organisms; The storage and preservation of meat (temperature and moisture control, and direct microbial inhibition); The eating quality of meat; meat and human nutrition; prefabricated meat.